Concordance Between Rapid On-Site Evaluation and Final Cytologic Diagnosis in Patients Undergoing Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration for Non-Small Cell Lung Cancer Staging. Issue 2 (16th October 2019) - Caupena, Cristina; Esteban, Lluis; Jaen, Angels; Barreiro, Bienvenido; Albero, Raquel; Perez-Ochoa, Francisco; Pontes De Souza, Patricia; Gibert, Oriol; Ferrer, Carme; Forcada, Pilar; García, Federico; Tarroch, Xavier; et al.
Abstract: Objectives: In patients with lung cancer undergoing mediastinal staging through endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA), decisions are based on rapid on-site evaluation (ROSE) findings. We aimed to analyze the concordance rate between ROSE diagnosis and final diagnosis. Methods: A prospective study was carried out in patients undergoing EBUS-TBNA for lung cancer staging. Diagnosis concordance was defined as cases where lymph nodes (LNs) presented the same diagnosis in ROSE and final diagnosis. Determinants of concordance were analyzed. Results: Sixty-four patients were included and 637 LNs sampled. ROSE diagnosis was concordant with final diagnosis in 612 (96.1%) LNs and nonconcordant in 25 (3.9%). Differences in the concordance rate were found between pathologists, ROSE diagnoses, presence of cell block, number of passes, and number of slides. The staging status was changed between ROSE and the final diagnosis in three (4.6%) patients. Conclusions: ROSE diagnosis has a high concordance with the final diagnosis.